Cytogenetic Abnormalities and Y Chromosome Microdeletions in Azoospermic and Oligospermic Infertile Males from West of Iran - Shaveisi-Zadeh, Farhad; Davarian, Kimia; Movafagh, Abolfazl; Mirfakhraie, Reza; Rostami-Far, Zahra; Alibakhshi, Reza; Abdi, Hossain; Bakhtiari, Mitra (Archives of Advances in Biosciences, 2017)
About 15% of couples have infertility problems, half of which are related to male factors. Cytogenetic and genetic disorders account for about 10% of the male infertility problems. The aim of this study was to determine the frequency and types of both cytogenetic abnormalities and AZF microdeletions of Y chromosome in idiopathic azoospermic and oligospermic infertile men in west of Iran. In this case-control study, a total of 108 infertile men including 62 azoospermic and 46 oligospermic men were studied for the cytogenetic and AZF microdeletions. Moreover, 90 fertile men served as a control group. Detailed clinical and laboratory examination was done for all participants. Karyotyping was done on peripheral blood lymphocytes to detect the cytogenetic abnormalities; likewise, multiplex-PCR method was performed to identify the presence of microdeletion in AZFa, AZFb or AZFc regions. Chromosomal abnormalities were detected in 6.5% (7/108) of cases, including two oligospermic men with balanced autosomal rearrangements, one oligospermic and four azoospermic men with Klinefelter syndrome. Y chromosome microdeletions were detected in 4.6% (5/108) of infertile men (AZFc: 3.7%, AZFbc: 0.9%). No AZFa deletion was detected in any of the patients. No chromosomal abnormality and Y chromosome microdeletion was detected in control group. The prevalence of chromosomal abnormalities and Y chromosome microdeletions shows the importance of genetic factors in male infertility. The analysis of karyotype and Y microdeletions in infertile men provide a proper understanding about the causes of infertility, the choice of the appropriate assisted reproduction technique and reducing the risk of transmission of these genetic defects to the future generation.